Sleep Disorders - K Pavlova, Milena; Latreille, Véronique (The American journal of medicine, 2019)
Sleep disorders are frequent and can have serious consequences on patients' health and quality of life. While some sleep disorders are more challenging to treat, most can be easily managed with adequate interventions. We review the main diagnostic features of 6 major sleep disorders (insomnia, circadian rhythm disorders, sleep-disordered breathing, hypersomnia/narcolepsy, parasomnias, and restless legs syndrome/periodic limb movement disorder) to aid medical practitioners in screening and treating sleep disorders as part of clinical practice.